2019
DOI: 10.1016/j.asmr.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

3-Dimensional Printed Models May Be a Useful Tool When Planning Revision Anterior Cruciate Ligament Reconstruction

Abstract: The authors report the following potential conflicts of interest or sources of funding: Funding for this project was provided by the UPMC Department of Orthopedic Surgery Chairman's fund. A.G. reports nonfinancial support from Axial3D. V.M. reports other from Smith & Nephew. Full ICMJE author disclosure forms are available for this article online, as supplementary material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…The authors found that a high-resolution 3D turbo spin echo proton density MRI sequence could quantitatively evaluate the location and orientation of previous bone tunnels for routine postoperative assessment, presurgical planning, and outcome evaluation [37]. With the same goal of improving preoperative planning in ACLR revision surgery, Kitamura et al found that 3D printed models of the knee were a useful addition to CT scans for sports medicine orthopedic fellows during the planning of ACLR revision surgery [38]. Most of these studies dealing with preoperative planning of ACLR revision have focused on accurately determining the size, location, and orientation of previous bone tunnels; this is certainly one of the first aspect to consider when approaching ACLR revision surgery, together with ruling out possible comorbidities responsible for ACL failure (i.e., lower limb malalignment, meniscal deficiency, previously overlooked concomitant knee instabilities).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that a high-resolution 3D turbo spin echo proton density MRI sequence could quantitatively evaluate the location and orientation of previous bone tunnels for routine postoperative assessment, presurgical planning, and outcome evaluation [37]. With the same goal of improving preoperative planning in ACLR revision surgery, Kitamura et al found that 3D printed models of the knee were a useful addition to CT scans for sports medicine orthopedic fellows during the planning of ACLR revision surgery [38]. Most of these studies dealing with preoperative planning of ACLR revision have focused on accurately determining the size, location, and orientation of previous bone tunnels; this is certainly one of the first aspect to consider when approaching ACLR revision surgery, together with ruling out possible comorbidities responsible for ACL failure (i.e., lower limb malalignment, meniscal deficiency, previously overlooked concomitant knee instabilities).…”
Section: Discussionmentioning
confidence: 99%
“…Using the same 3D printer and freeware, a bone prosthesis of the frontal process (zygomatic bone), the zygomatic process (temporal bone), and a portion of the parietal bone were fabricated for craniofacial reconstruction [45]. The femur (right distal) and proximal tibia were segmented, and 3D printed using a Formlabs Form 2 3D printer for planning revision ligament (anterior cruciate) reconstruction [46]. The anatomy comprising the femoral artery, vein, pelvis, and cuboid mold encasing and supporting the structures for ballistic gel soft tissue casting was 3D printed using a Formlabs Form 2 3D printer [47].…”
Section: Anatomic Modelsmentioning
confidence: 99%
“…While the addition of 3D printed models did not significantly impact agreement for attending orthopedic physicians, it did lead to a higher agreement rate (76%) for fellow physicians compared to CT images alone (63%) (p = 0.050). Overall, fellow physicians had a higher agreement rate (74%) with the 3D printed models than with CT alone (65%) (p = 0.049) [46]. Clinicians and researchers have found that 3D printed models of coronary artery anomalies developed from CT data are useful in visualizing coronary artery anatomy and their abnormalities and complement viewing 3D CT scans [51].…”
Section: Surgical Guides and Surgical Planningmentioning
confidence: 99%
“…These reconstructions have also been used to print 3D models to facilitate planning complex revision cases. 40,57…”
Section: Radiographic Evaluation and Classificationmentioning
confidence: 99%
“…These reconstructions have also been used to print 3D models to facilitate planning complex revision cases. 40,57 A simple classification system has been developed and validated using 3D CT images to characterize femoral tunnel position (Table 1). 46 Characterization of tunnel position using this system reveals an alarming number of partially anatomic tunnels, with major implications for revision surgery.…”
Section: Computed Tomographymentioning
confidence: 99%